EXTRACTION OF ROOF LINES FROM HIGH-RESOLUTION IMAGES BY A GROUPING METHOD - Dal Poz, A. P. [UNESP]; Fernandes, V. J. M. [UNESP]; Halounova, L.; Schindler, K.; Limpouch, A.; Pajdla, T.; Safar, V; Mayer, H.; Elberink, S. O.; Mallet, C.; Rottensteiner, F.; Bredif, M.; et al. (Copernicus Gesellschaft Mbh, 2016)
This paper proposes a method for extracting groups of straight lines that represent roof boundaries and roof ridgelines from high-resolution aerial images using corresponding Airborne Laser Scanner (ALS) roof polyhedrons as initial approximations. The proposed method is based on two main steps. First, straight lines that are candidates to represent roof ridgelines and roof boundaries of a building are extracted from the aerial image. Second, a group of straight lines that represent roof boundaries and roof ridgelines of a selected building is obtained through the optimization of a Markov Random Field (MRF)-based energy function using the genetic algorithm optimization method. The formulation of this energy function considers several attributes, such as the proximity of the extracted straight lines to the corresponding projected ALS-derived roof polyhedron and the rectangularity (extracted straight lines that intersect at nearly 90 degrees). Experimental results are presented and discussed in this paper.
Keywords: Markov Random Field; ALS; Straight line